Synthesis of Porphyrin Zr-MOFs for the Adsorption and Photodegradation of Antibiotics under Visible Light - Zong, Yuqing (ACS Omega, 2021)
[Image: see text] The release of antibiotics into the water environment can pose a serious threat to human and ecological health, so it is of great significance to effectively remove antibiotics from wastewater. In this work, porphyrinic zirconium metal–organic framework material, PCN-224, was first explored for the adsorption removal of antibiotics from water using tetracycline (TC) and ciprofloxacin (CIP) as examples. We prepared a series of PCN-224 with different particle sizes (150 nm, 300 nm, 500 nm, and 6 μm). Benefiting from the huge surface area (1616 m(2) g(–1)), the 300 nm-PCN-224 sample had the best adsorption properties for TC and CIP. Remarkably, it exhibits fast removal rates and high adsorption capacities of 354.81 and 207.16 mg g(–1) for TC and CIP, respectively. The adsorption of TC and CIP in 300 nm-PCN-224 is consistent with the pseudo-second-order kinetic model and Langmuir isotherm model, which indicates that the adsorption can be regarded as homogeneous monolayer chemisorption, and the adsorption is exothermic, which has been confirmed by thermodynamic studies. Under visible-light irradiation, 300 nm-PCN-224 exhibited high photocatalytic activity for TC and CIP. The adsorption studies confirmed that the adsorption of adsorbates takes place via the formation of hydrogen bonding, π–π interactions, and electrostatic attraction. In addition, the adsorbent can be simply regenerated by photocatalysis under visible light, and the adsorption–desorption efficiency is still above 85% after repeated use five times. The work of MOFs to remove antibiotics from water shows that MOFs have great potential in this field and are worthy of further study.